Pengaruh Kecerdasan Emosional dan Motivasi Belajar terhadap Kemampuan Berpikir Kritis Matematika - Putri Sulistianingsih (Universitas Indraprasta PGRI, 2016)
This survey research with regression analysis is aimed at 1) acknowledging the impacts of both emotional question and study motivation on mathematical critical thinking ability all together 2) acknowledging the impacts of emotional question on mathematical critical thinking ability 3) acknowledging the impacts of study motivation on mathematical critical thinking ability. The research was conducted at SMA Negeri 83 Jakarta in 2015/2016 by using simple random sampling with 154 respondents taken from the number of affordable population reach as many as 250 respondents. The instrument used is questionnaire on variables of emotional question and study motivation, and essay test for mathematical critical thinking ability which all instruments points have been empirically validated. Hypothesis is conducted after the data fulfill in series of classic assumption test, i.e. normality test, linearity test and multicollinearity test. The research result show that 1) there are significant impacts of both emotional question and study motivation all together on mathematical critical thinking ability; 2) there are significant impacts of emotional question on mathematical critical thinking ability; 3) there are significant impacts of study motivation on mathematical critical thinking ability.